Architecture Militaire du Deccan Une Réponse défensive Face à la Guerre Moderne. - Morelle, Nicolas (Archaeopress, 2021)
Using the most recent investigative techniques, such as photogrammetry and 3D modeling, this volume presents a wealth of new data on the military architecture of the Deccan region in central India between the medieval and modern period.